Teaching Feelings Assigned to the Teaching of Formative Research in an Education Faculty - Turpo Gebera, Osbaldo (2020)
In the teaching of formative research a series of subjective constructions about their understanding and transcendence are raised. This situation encourages the determination of the meanings assigned to their pedagogical implementation in teacher training. In that intention, we have interviewed 20 teachers from an education faculty of a public university in Peru, in order to recognize the senses in their conception, their distinction in scientific research, their characteristics and expectations. The results show that teachers express a diversity of educational meanings, later in the training of researchers as a teaching device or strategy; Likewise,the terms of research research are distinguished in the strict sense, which induces overlaps or continuities between them; On the other hand, emphasize the development of cognitive skills linked to research, and finally, Situate in the training process ofresearch, the different expectations of realization not always specified in teaching. The approach to the senses assigned to formative research evidenced differentiations, confusions, but also coincidences on the formative nature of the research, which entails a way of thinking about the best management of teaching problems and of society.